2017
DOI: 10.1111/sltb.12424
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationships Between Positive Affect, Loneliness, and Suicide Ideation: Age‐Specific Factors in a General Population

Abstract: The aims of this study were to analyze whether positive and negative affect, social support, and loneliness are factors longitudinally related to suicide ideation in the general population in different age groups. A total of 2,392 individuals from a nationally representative sample of the Spanish general population were evaluated in 2011-2012 and in 2014-2015. After including relevant control variables in the analyses, lower positive affect was prospectively related to ideation in 18- to 59-year-old individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 45 publications
(71 reference statements)
3
38
0
Order By: Relevance
“…The interpersonal theory of suicide (Van Orden et al, 2010) hypothesizes that suicidal ideation occurs when subjects experience a combination of two interpersonal constructs: low belongingness (or social disconnection) and high burdensomeness. Loneliness (i.e., feeling of emptiness, isolation, or unwanted solitude) has been positively associated with suicidal ideation (Bennardi et al, 2017) and negatively with gratitude (Caputo, 2015). In fact, gratitude aims at increasing stable connection feelings with others without attachment (Sahdra, Shaver, & Brown, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interpersonal theory of suicide (Van Orden et al, 2010) hypothesizes that suicidal ideation occurs when subjects experience a combination of two interpersonal constructs: low belongingness (or social disconnection) and high burdensomeness. Loneliness (i.e., feeling of emptiness, isolation, or unwanted solitude) has been positively associated with suicidal ideation (Bennardi et al, 2017) and negatively with gratitude (Caputo, 2015). In fact, gratitude aims at increasing stable connection feelings with others without attachment (Sahdra, Shaver, & Brown, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Expectation for the future may remain negative even when experiencing optimism for a given life experience (Gillham, Shatte, Reivich, & Seligman, 2001). Loneliness (i.e., feeling of emptiness, isolation, or unwanted solitude) has been positively associated with suicidal ideation (Bennardi et al, 2017) and negatively with gratitude (Caputo, 2015). In a sample of 284 college students, optimism weakened the relationship between hopelessness and suicidal ideation, over the influence of depressive symptoms (Hirsch & Conner, 2006) The interpersonal theory of suicide (Van Orden et al, 2010) hypothesizes that suicidal ideation occurs when subjects experience a combination of two interpersonal constructs: low belongingness (or social disconnection) and high burdensomeness.…”
Section: Ta B L E 3 Changes In Psychological Measures Between Pre Joumentioning
confidence: 99%
“…Identifying robust risk factors for suicidal behaviour is methodologically challenging for a number of reasons, not least because suicide is a rare event (Klonsky et al, 2016; Stickley and Koyanagi, 2016). Most studies of loneliness and suicidal behaviour have used self-reported measures of suicidality (Bennardi et al, 2019), which may be prone to reporting biases (Beutel et al, 2017; Stickley and Koyanagi, 2016), and only a few studies (mostly case-control studies) have investigated loneliness as a potential cause of deaths by suicide (Courtin and Knapp, 2017; Holt-Lunstad et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of loneliness is defined as a discrepancy between current social relationships and individual preference; the discrepancy leads to a negative experience of feeling alone, and dysphoria of feeling socially isolated, even when the person is accompanied by family and friends (27). In this perspective, loneliness is an independent phenomenon of depression with well-defined dimensions (28).…”
Section: Discussionmentioning
confidence: 99%